Consumer Fraud: Older People's Perceptions and Experiences. Issue 1 (2nd January 2021) - Segal, Michal; Doron, Israel (Issi); Mor, Sagit
ABSTRACT: In view of the growing need to address the rights of older people as consumers, this study captures the perceptions and meanings that older people attribute to their experiences as older consumers, particularly regarding consumer fraud, using qualitative-phenomenological methodology based on semi-structured, open-ended interviews with 16 older consumers in Israel. The findings raise distinctive aspects of their experiences, including physical and cognitive characteristics of aging, social response to aging, and involvement of family members in decision making and support. The study concludes by offering several sociolegal policy recommendations for protecting older consumers, directed to them, their family members, professionals interacting with them, and the legal system.